2018
DOI: 10.3748/wjg.v24.i10.1107
|View full text |Cite|
|
Sign up to set email alerts
|

Maturity of associating liver partition and portal vein ligation for staged hepatectomy-derived liver regeneration in a rat model

Abstract: AIMTo establish a rat model for evaluating the maturity of liver regeneration derived from associating liver partition and portal vein ligation for staged hepatectomy (ALPPS).METHODSIn the present study, ALPPS, partial hepatecotmy (PHx), and sham rat models were established initially, which were validated by significant increase of proliferative markers including Ki-67, proliferating cell nuclear antigen, and cyclin D1. In the setting of accelerated proliferation in volume at the second and fifth day after ALP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 38 publications
1
6
0
1
Order By: Relevance
“…In the early proliferative stage after ALPPS-stage 1, the increase in volume is the result of proliferation of hepatocytes that are enlarged but have not yet undergone full maturation. 20,21 As hepatocytes mature, the functional increase will likely catch up with the volume increase. Of note, the differentiation of hepatocytes in ALPPS appears to be more prolonged than after hepatectomy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the early proliferative stage after ALPPS-stage 1, the increase in volume is the result of proliferation of hepatocytes that are enlarged but have not yet undergone full maturation. 20,21 As hepatocytes mature, the functional increase will likely catch up with the volume increase. Of note, the differentiation of hepatocytes in ALPPS appears to be more prolonged than after hepatectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, the differentiation of hepatocytes in ALPPS appears to be more prolonged than after hepatectomy. 20 Whether the dynamics of these growth patterns are comparable in patients undergoing PVE remains unknown. In this study, the first measurement of both volume and function was conducted 3 weeks after PVE.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the authors observed a similar increase in FLV to the ALPPS group, indicating that localized trauma or inflammatory responses might accelerate the induction of hepatocyte proliferation (19). Almau et al (36) and Tong et al (37) established a rat experimental model based on the ALPPS procedure as described above. Furthermore, Yao et al (38) revealed that the reactivation rate of the liver was significantly faster in the ALPPS group on the 3rd and 7th postoperative days compared with the PVL group.…”
Section: Discussionmentioning
confidence: 99%
“…The fibrotic tissue ends up hindering liver regeneration (72). Although previous cirrhosis would limit in principle the process of hypertrophy, the degree of hypertrophy induced by ALPPS could be beneficial even for cirrhotic patients (59,73,74). However, discordance between the growth in liver volume in ALPPS and the functional growth of the proliferated liver has been detected, with multiple signs of immaturity in the tissue being appreciated (73,(75)(76)(77).…”
Section: Alpps and Histology Featuresmentioning
confidence: 99%